OPPORTUNITIES OF DEVELOPMENT OF TOURIST DESTINATIONS IN THE CONTEXT OF SUSTAINABLE TOURISM (Proceedings of the YSU C: Geological and Geographical Sciences, 2023)
The article explores the essence and modern significance of tourist destinations. The purpose of the work is to identify the prerequisites for the development of a tourist destination in the context of sustainable tourism. The sustainable management of the tourist destination was also considered as being responsible for the development of the destination itself.
Keywords: tourism destination; sustainable development; sustainable tourism; sustainable destination management